Occurrence, body mass and biomass of Syntermes spp. (Isoptera: Termitidae) in Reserva Ducke, Central Amazonia - Martius, Christopher (Acta Amazonica, 1998)
The leaf-feeding species Syntermes molestus and S. spinosus are two dominant termite species in Reserva Ducke in Central Amazonia; two other species (S. aculeosus, S. longiceps) exist in the area. All species except S. aculeosus were also found in urban areas. The workers of S. molestus and S. spinosus have average body dry weights of 4.5±0.2 and 13.1±1.4 mg, and the weight of their soldiers is 8.2±0.2 and 51.0±1.7 mg, respectively. Therefore, S. spinosus is among the largest termites of the world. In both species, fresh weight is about 4.7 higher than dry weight (a wider relation than in other termite species). The biomass of the populations of both species amounted to about 1 g m-2 (dry weight; indirect estimate), which rises previous assessments of the total termite biomass by about 36-45%, to a value of 3.0-3.5 g m-2.
Ocorrência, massa corporal e biomassa de espécies de Syntermes (Isoptera: Termitidae) na Reserva Ducke, Amazônia Central
Keywords: Amazon Rainforest; Leaf-feeding Termites; Body Mass; Biomass; Floresta Amazônica; Cupins Comedores De Folhas; Massa Corporal; Biomassa